STEM education: Vocational teacher’s perspective of 21st Century - Rabiman, Rabiman; Widarto, Widarto; Nurtanto, Muhammad; Kholifah, Nur (International Journal of Psychosocial Rehabilitation, 2020)
STEM education is widely adopted and has a positive impact on developed countries. Constructive and focused on STEM education in Indonesia, starting in 2019. But STEM must be held in facing the challenges of the 21st century. This study aims to examine vocational teacher perceptions related to understanding STEM in Indonesia. A total of 157 vocational teachers were involved in the research questions (RQ). Open and closed questionnaires represent the expression of their perceptions when implementing STEM learning. The results of the study illustrate that STEM needs to be improved continuously and continuously. Researchers need to focus on vocational teachers as an essential role in the success of new learning reforms. However, the involvement of parties can accelerate positive thinking about STEM learning in the vocational field.